68Ga-DOTATATE PET/MR Imaging of Urinary Bladder Paraganglioma. (August 2015) - Sajjan, Rakesh S.; Gavra, Maria; Agrawal, Kanhaiyalal; Syed, Rizwan; Bomanji, Jamshed
Abstract : Abstract: Paragangliomas of the urinary bladder are very rare. They are extra-adrenal autonomic nervous system tumors. This report presents a case of a 13-year-old boy with urinary bladder paraganglioma and the role of somatostatin receptor imaging with simultaneous positron emission tomography magnetic resonance (PET/MR). We have also described appearances of iodine-123 metaiodobenzylguanidine ( 123 I-MIBG) single photon emission computed tomography (SPECT/CT) in comparison to somatostatin receptor imaging.